CD4+ T Responses Other Than Th1 Type Are Preferentially Induced by Latency-Associated Antigens in the State of Latent Mycobacterium tuberculosis Infection - Yamashita, Yoshiro; Oe, Toshiyuki; Kawakami, Kenji; Osada-Oka, Mayuko; Ozeki, Yuriko; Terahara, Kazutaka; Yasuda, Ikkoh; Edwards, Tansy; Tanaka, Takeshi; Tsunetsugu-Yokota, Yasuko; Matsumoto, Sohkichi; Ariyoshi, Koya (Frontiers in Immunology, 2019)
Mycobacterium tuberculosis (M. tuberculosis) produces a diverse range of antigenic proteins in its dormant phase. The cytokine profiles of CD4+ T cell responses, especially subsets other than Th1 type (non-Th1 type), against these latency-associated M. tuberculosis antigens such as α-crystallin (Acr), heparin-binding hemagglutinin (HBHA), and mycobacterial DNA-binding protein 1 (MDP-1) remain elusive in relation to the clinical stage of M. tuberculosis infection. In the present study, peripheral blood mononuclear cells (PBMCs) collected from different stages of M. tuberculosis-infected cases and control PBMCs were stimulated with these antigens and ESAT-6/CFP-10. Cytokine profiles of CD4+ T cells were evaluated by intracellular cytokine staining using multicolor flow cytometry. Our results demonstrate that Th1 cytokine responses were predominant after TB onset independent of the type of antigen stimulation. On the contrary, non-Th1 cytokine responses were preferentially induced by latency-associated M. tuberculosis antigens, specifically IL-10 response against Acr in latent M. tuberculosis infection. From these results, we surmise a shift in the CD4+ T cell response from mixed non-Th1 to Th1 dominant type during TB progression.